Solid waste management challenges for cities in developing countries - Morales-Cayax, Miguel Ángel (2015)
The target was raised to identify areas for their condition, significance or cultural significance need to be protected, preserved or restored. By performing an agroecological zoning and landscape. The ecological or eco-regionalization consists of defining relatively homogeneous geographic areas based on the physical and biological environment, so as to establish appropriate links with the use and appropriation of land by the society. Terrain, climate and soils: physical characterization of three important aspects was performed. Map of morphometric relief units and is based on a semi-automated obtained from a digital elevation model and shape of curves. Agro-Ecological Zones Map is the product of crossing geomorfopedology map units (relief + soils) with the map of climates. The map Vegetation Cover and Land Use: prepared from satellite imagery, performing a supervised classification by means of spectral signatures. The Landscape Map: Crossing the Agro-Ecological Zones map of the Vegetation Cover and Land Use. It is noted that the most important landscapes by extension in the watershed are: a. Plain / Alfisols / CB ‘ with 20.49% Construction b. Mountain / Andisols / BB ‘2 with 17.23% Mixed Forest c. Plain / Alfisols / CB ‘with 8.66% Annual Agriculture d. Mountain / Andisols / BB ‘2 with Permanent Agriculture 8.13% In the upper part of the basin has prevalence of mixed forest and permanent agriculture; while in the lower part has a greater area of urbanization and agriculture annual.